The principles of uncertainty - Kalman, Maira 1949- (Penguin Books, 2009)
The Principles of Uncertainty is an irresistible invitation to experience life through the psyche of Maira Kalman, one of this country's most beloved artists. The result is a book that is part personal narrative, part documentary, part travelogue, part chapbook, and all Kalman. Her brilliant, whimsical paintings, ideas, and images--which initially appear random--ultimately form an intricately interconnected worldview, an idiosyncratic inner monologue. Kalman contends with some existential questions--What is identity? What is happiness? Why do we fight wars? And then, of course, death, love, and candy (not necessarily in that order)
Includes index
Originally published: New York : Penguin Press, 2007. - Includes index
Keywords: Kalman, Maira / Philosophy; Kalman, Maira / Travels; Kalman, Maira / Political and social views; Illustrators / Biography / United States